The addressee of food advertising. Selected legal issues - Łata, Monika (Przegląd Prawa Rolnego, 2020)
The aim of the considerations is to answer the question whether the existing legal regulations correctly identify and take into account the diversity of addressees of food advertising. The authoress concludes, among other things, that the current legal regulations do not identify or sufficiently differentiate the addressees of food advertising. The notion of “final consumer” from Regulation 178/2002 allows to cover both persons buying food and persons consuming food, which is crucial in the context of food law objectives. However, the protection of the consumer by information excludes from this group those who lack a sufficient level of awareness and mental maturity. The model of an average consumer developed by the CJEU also does not support correct identification of the addressee of food advertising. Therefore, it should be postulated to "differentiate the food consumer model" by constructing a more flexible definition of the final consumer or even a definition of the addressee of food advertising.